Market reaction to political and national budget announcements in the period 1981-2011 : The Malaysian evidence / Ho Swee Jack - Ho, Swee Jack (2012)
Political and national budget announcements have been widely believed to be able to affect the stock market movement. The purpose of this research project is to examine empirically whether the political and national budget announcements create any significant impact to the Malaysian stock market despite numerous anecdotal claims that hint at this possibility. Through the analysis, this research further intends to justify whether the Efficient Market Hypothesis (EMH) is supported within Malaysian context, i.e. whether the stock price is efficient in reflecting information content in the announcements. In addition, the stock market behavior during the period of study, namely overreaction and momentum, can also be determined from the analysis results. Event study methodology has been employed as the analysis technique of this study. 38 political announcements from the past 30 years have been selected arbitrarily together with 15 budget announcements starting from 1998. An 11-day event window has been formed around each announcement date to study the significance of abnormal return. The study results show that the Malaysian stock market generally reacts significantly to both positive and negative political announcements and only positive budget announcements in general. The market, however, does not react to certain types of political events. Besides, the stock market behavior supports one of the following theories—Efficient Market Hypothesis, Uncertain Information Hypothesis, Overreaction Hypothesis and Momentum Hypothesis—based on the type of announcements released.